Relation between Ossicular Erosion and Destruction of Facial and Lateral Semicircular Canals in Chronic Otitis Media - Bulğurcu,Suphi (2017)
Abstract Introduction Chronic otitis media can cause multiple middle ear pathogeneses. The surgeon should be aware of relation between ossicular chain erosion and other destructions because of the possibility of complications. Objective This study aimed to investigate the rates of ossicular erosion in cases of patients with and without facial nerve canal destruction, who had undergone mastoidectomy due to chronic otitis media with or without cholesteatoma. Methods We retrospectively analyzed three hundred twenty-seven patients who had undergone tympanomastoidectomy between April 2008 and February 2014. We documented the types of mastoidectomy (canal wall up, canal wall down, and radical mastoidectomy), erosion of themalleus, incus and stapes, and the destruction of facial and lateral semi-circular canal. Results Out of the 327 patients, 147 were women (44.95%) and 180 were men (55.04%) with a mean age 50.8 ± 13 years (range 8-72 years). 245 of the 327 patients (75.22%) had been operated with the diagnosis of chronic otitis media with cholesteatoma. FNCD was present in 62 of the 327 patients (18.96%) and 49 of these 62 (79.03%) patients had chronic otitis media with cholesteatoma. The correlation between the presence of FNCD with LSCC destruction and stapes erosion in chronic otitis media with cholesteatoma is statistically significant (p < 0.05). Conclusion Although incus is the most common of destructed ossicles in chronic otitis media, facial canal destruction is more closely related to stapes erosion.